Polimorfismo MTHFR asociado a Enfermedad Tromboembólica Venosa - Flores Sandí, Grettchen (2019)
Venous thromboembolic disease is rarely associated with hereditary thrombophilia, which can be classified into two main categories: loss of function mutations (antithrombin III, protein C, protein S) and gain-of-function mutations (prothrombin gene mutation). G20210A), MTHFR mutation, Factor VIII, Factor V Leiden). We present the case of a young man with chronic thromboembolic pulmonary hypertension (CTEPH) and heterozygosity in the MTHFR gene, which exemplifies the possibility of assessing this pathology in a specialized medical consultation that is not vascular, hematological or rheumatological; and given the clinical evolution and high medical care costs of these patients, justifies the review of the etiopathogenesis and clinical consequences of this polymorphism, which causes a homocysteine-methionine imbalance that influences reactions of cell proliferation, protein synthesis, synthesis of RNA and methylation processes of DNA and other substances at the cellular level. However, its association with thromboembolism is controversial and it has not been possible to confirm a significant association between hereditary thrombophilia and CTEPH. Complications such as that presented in the case described with the development of right heart failure, in a patient not endarterectomy tributary, acquire legal and ethical medical relevance, not only because of the possibility of prescribing medical treatment and its cost for social security, but also because its effect on survival, which demonstrates the importance of studies for the development of new prophylactic and therapeutic drugs and genetic counseling in cases of a genetically determined tendency to venous thromboembolic disease.